Novel approaches to control malaria in forested areas of Southeast Asia - Von Seidlein, L; Peto, T; Tripura, R; Pell, C; Yeung, S; Kindermans, J; Dondorp, A; Maude, R (Elsevier, 2019)
The emergence and spread of drug resistance in the Greater Mekong Subregion (GMS) have added urgency to accelerate malaria elimination while reducing the treatment options. The remaining foci of malaria transmission are often in forests, where vectors tend to bite during daytime and outdoors, thus reducing the effectiveness of insecticide-treated bed nets. Limited periods of exposure suggest that chemoprophylaxis could be a promising strategy to protect forest workers against malaria. Here we discuss three major questions in optimizing malaria chemoprophylaxis for forest workers: which antimalarial drug regimens are most appropriate, how frequently the chemoprophylaxis should be delivered, and how to motivate forest workers to use, and adhere to, malaria prophylaxis.